Social exclusion from peer interaction and relationships in a daycare center a micro-ethnography - Paavilainen, Aleksi (2017)
This study investigates social exclusion from peer interaction and relationships among children in one Finnish daycare center. Social exclusion is a multifaceted phenomenon that can be encountered as a result of for instance peer exclusion or social withdrawal. Persistent social exclusion can have severe negative consequences. However, social exclusion is also an inevitable part of social life. This study discusses the multiplicity of this phenomenon in one daycare center. This study is a micro-ethnography. I wrote notes and video-recorded the everyday life of two child groups for 12 days. I analyzed the data by revealing how the context partly created the social exclusions occurring there. I paid special attention on free play times. Children encountered social exclusion from peer interaction and relationships differently: Most children appeared to only encounter it momentarily and not very intensively, whereas some children appeared to encounter it persistently and more intensively than the other children. Most children encountered this kind of social exclusion mostly due to peer exclusion, whereas some children appeared to mostly socially withdraw from their peers. Free play times inside and outside differed from each other, but the entire daycare center space affected social exclusions occurring in both locations: An explicit rule of ‘everyone should play with everyone’ was always present as well as a more implicit rule of ‘how boys and girls should behave.’ Boys, who I perceived to perform non-hegemonic masculinity, appeared to be vulnerable to experience persistent social exclusion in my data.